The lived experience of spiritual abuse - Ward, David J. (Mental health, religion & culture, 2011)
Over the years there has been considerable research investigating the controversial issues of cult recruitment, "mind control" and post-group difficulties of ex-members from a variety of religious groups. However, the less-well-defined phenomenon of "spiritual abuse" is still under-researched as a specific phenomenon. This is particularly evident in the lack of studies exploring the subjective, internal experience. This study reports on the lived experiences of six individuals who left five different religious groups that were essentially Judeo-Christian in their orientation. An Interpretative Phenomenological Analysis (IPA) revealed six core themes throughout the participant narratives. They consist of "Leadership representing God," "Spiritual bullying," "Acceptance via performance," "Spiritual neglect," "Manifestation of internal states," and "Expanding external/internal tension." These are offered as a foundation to answer the question What can be described as the lived experience of spiritual abuse? The findings suggest that spiritual abuse is a multi-faceted and multi-layered experience that is both process and event, affecting the bio/psycho/social and spiritual domains of an individual.